The Effect of Transformational Leadership and Work Culture on Teacher Performance: The Mediating Role of Work Motivation - Riyanto Dwi Utomo; Sungkowo Edy Mulyono (Universitas Negeri Semarang, 2026)
This study aims to analyze the influence of transformational leadership and work culture on teacher performance, both directly and indirectly through teacher work motivation at State Vocational High Schools in Sukoharjo Regency. This study used a quantitative approach with a survey method. The study population was 438 teachers, with 209 respondents determined using probability sampling techniques. Data collection was carried out through a questionnaire using a Likert scale of 1–5. Data analysis was carried out using IBM SPSS through validity tests, reliability tests, descriptive analysis, regression analysis, path analysis, and mediation tests. The results showed that transformational leadership and work culture had a positive and significant effect on teacher work motivation and performance. Work motivation also had a positive and significant effect on teacher performance. In addition, work motivation was proven to be able to significantly mediate the influence of transformational leadership and work culture on teacher performance. These findings indicate that improving the quality of the principal's transformational leadership and strengthening a positive work culture can increase teacher work motivation, which ultimately has an impact on improving teacher performance. This study provides insights for school administrators in designing policies that focus on development, leadership, work culture, and work motivation to improve teacher performance.